Evaluation of reproduction performance of Gir cattle (Bos indicus) reared in Hot-Humid condition of Konkan region - AJ Mayekar,; DN Yadav,; Shalu Kumar,; BG Desai,; RG Burte,; JS Dhekale, (Journal of Livestock Biodiversity, 2025)
The study was conducted at Dr. B.S. Konkan Krishi Vidyapeeth Dapoli, Maharashtra to assess the reproductive efficiency of Gir cattle. A total of 226 Gir cows were selected and their information regarding reproductive parameters were collected from farm records (Bombay Gorakshak Mandali, Akurli Road, Kandivali (East) Mumbai, Maharashtra) for a period of 26 years (1981 to 2005). Data representing 226 Gir cows from 1090 total records of reproductive parameters for a period of 25 years (1981 to 2005) were analysed to determine Body weight (BW), age at puberty (AP), age at first calving (AFC), service period (SP), calving interval (CI), gestation period (GP), dry period (DP), weight at first calving, reproductive and breeding ef~iciency (%). The overall least squares means of age at puberty (979.08±12.77 days), age of first calving (1254.29±12.83 days), service period (107.93±0.64 days), calving interval (387.26±0.63 days), gestation period (279.86±0.20 days), dry period (87.74±0.95 days), weight at first calving (352.63±1.64 kg), with reproductive and breeding ef~iciency and persistency index, 40.70±0.11 per cent and 89.29±0.40 per cent, respectively. Therefore, it can be concluded that Gir cattle shows optimum reproductive performance under Konkan region of Maharashtra.